Development of a Referral System to Optimize Centers for Character Development and Counseling Guidance as Well as Psychological Service Centers for Professional Learning and Development Institutions - ‪Bachtiar Sjaiful Bachri; Himawan Wismanadi; Umi Anugerah Izzati; Miftakhul Jannah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
The research aims to determine the implementation of the referral system at the Centers for Character Development and Counseling Guidance (CCDGC) and Psychology Service Centers. This study uses a type of R&D with a descriptive approach. The participants in this research are the chairperson or secretary at the Center for Psychological Services, the CCDCG, and related parties in the internal referral system and system developers. Data analysis in the form of observation, documentation, and focus group discussion (FGD) was collected directly. This study's results indicate that the referral system carried out by the CCDCG can be implemented as needed. In addition, the Psychological Service Center in the psychological examination and consultation program can develop a referral system according to the needs of clients from outside the Universitas Negeri Surabaya (UNESA). This study implies that the implementation of the referral system makes it easier for users to access services according to their needs, and the psychology service center has an optimized SOP to rule the CCDCG at UNESA. The limitation of this study is that it is only focused on UNESA. Hence, further research can analyze the development of a referral system in the CCDCG to other institutions and compare it to UNESA.